A causal model of leader ethical behavior and radical innovation: the mediating effect of leader identification and the moderating effect of promotion focus - Zhu, Lingfeng; Wang, Le; Jin, Xiu (Frontiers in Psychology, 2025)
IntroductionInnovation is essential for an organization's survival and growth, with radical innovation driving transformative change. Despite its significance, the mechanisms that foster employees' radical innovation remain underexplored. This study examines how leader ethical behavior influences radical innovation, offering a novel perspective on leadership's role in fostering innovation.MethodsA quantitative approach was employed, utilizing survey data from 371 employees of Chinese small and medium-sized enterprises (SMEs). Structural equation modeling (SEM) was applied to test the research model, which links leader ethical behavior to radical innovation, emphasizing the mediating role of leader identification and the moderating role of promotion focus.ResultsThe findings reveal that leader ethical behavior positively influences both leader identification and radical innovation. Furthermore, leader identification mediates the relationship between leader ethical behavior and radical innovation. Promotion focus strengthens the effects of leader ethical behavior on radical innovation, as well as the impact of leader identification on radical innovation.DiscussionThis study contributes to radical innovation research by integrating leader ethical behavior into the innovation discourse, extending theoretical perspectives beyond conventional drivers. The findings provide practical insights for organizations seeking to cultivate innovative work environments, enhance leader identification, and empower employees for radical innovation.